When William Met Mary: The Rewriting of Mary Lamb’S and William-Henry Ireland’S Stories in Peter Ackroyd’S The Lambs Of London - Chalupský, Petr (Studia Anglica Posnaniensia, 2013)
Peter Ackroyd’s London novels represent a distinctive component in his project of composing a literary-historical biography of the city. Understanding London as a multilayered palimpsest of texts, Ackroyd adds to this ongoing process by rewriting the city’s history from new, imaginative perspectives. For this he employs approaches and strategies such as parody, pastiche, genre mixture, metafiction, intertextuality and an incessant mixing of the factual with the fictititious. The aim of this article is to explore the various ways in which he toys with historical reality and blurs the borderline between fiction and biography in The Lambs of London (2004), offering thus an alternative rendering of two unrelated offences connected with late eighteenth and early nineteenth century London literary circles: Mary Lamb’s matricide and William-Henry Ireland’s forgeries of the Shakespeare Papers.